Functional constipation in schoolchildren and adolescents and its relationship with anxiety, quality of life and behavioral factors: systematic review and meta-analysis - Higuera Carrillo, Juanita Nathalie (2026)
Introduction: Functional constipation (FC) is a common problem in childhood. A bidirectional interaction within the brain gut axis has been described, as well as the presence of behavioural and emotional factors that may affect health-related quality of life (HRQoL). Objective: To evaluate the relationship between functional constipation and health-related quality of life, anxiety, and other behavioural factors in schoolchildren and adolescents. Materials and methods: A systematic review and meta-analysis was conducted of studies published between 1 January 2014 and March 2024 that evaluated the association between FC, HRQoL, anxiety, and other behavioural factors in the paediatric population. MeSH terms were used to search electronic databases in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Of 128 references identified, four articles were included (three case control studies and one cross-sectional study), comprising a total of 2,820 children aged between 2 and 18 years. Of these, 9.89% had FC and 88.6% did not have FC. Children with FC showed poorer HRQoL, particularly in the social domain, and obtained higher scores on scales such as Child-PAQ, CBCL/4–18, and SDQ, suggesting an association with emotional and behavioural problems, particularly increased anxiety and depression. The meta-analysis showed a higher overall PedsQL score, with high heterogeneity among the included studies. Conclusions: Functional constipation in children and adolescents is associated with behavioural factors that negatively impact health-related quality of life. The findings suggest a greater presence of anxiety and depression symptoms in this population. Future studies should consider more balanced distributions between cases and controls and evaluate other individual characteristics. These findings highlight the importance of a comprehensive clinical approach that addresses both digestive and emotional or behavioural aspects Keywords: Constipation; Quality of Life; Anxiety; Behavior; Students; Adolescent (source: MeSH NLM).